Asymmetrical Arbitration Clauses: A Comparative Study of International and Indonesian Arbitration Law - Jovanka Lingkanaya; Huala Adolf; Prita Amalia (Pandecta Research Law Journal, 2021)
This article presents a study of the validity of asymmetrical arbitration clauses, a clause that combines arbitration and a choice of court option, in international commercial contracts. These clauses designate a method of dispute settlement that gives a more favorable position for one of the parties to a contract, hence, creating a debate on its validity on an international level. Despite the convenience the trend has brought in business, this form of arbitration clause has been called into doubt by courts in numerous jurisdictions. Unfortunately, Indonesia itself has yet to have a firm legal standing on this matter as asymmetrical arbitration clauses are not explicitly regulated by the Indonesian arbitration law. This research is conducted by exploring the relation between theories and practices concerning asymmetrical arbitration clauses through analyzing case law and provisions of international arbitration law and the Indonesian arbitration law, and are also analyzed through principles of international and Indonesian contract law. This article aims to provide an analysis regarding the legal effects of having asymmetrical arbitration clauses in commercial contracts and commercial arbitration. Lastly, this study offers a method of interpretation towards such clauses that favors their validity under both international arbitration law and Indonesian arbitration law.